2017
DOI: 10.3389/fneur.2017.00637
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis on the Role of Cryptochromes in Inflammation and Subarachnoid Hemorrhage Outcome

Abstract: We have recently found that the temperature variability (TV) in the day–night cycle may predict the mean intracranial pressure in the following 24 h (ICP24) in subarachnoid hemorrhage (SAH) patients under multimodality monitoring, sedation, and hypothermia (<35°C). Specifically, we found that ICP24 = 6 (4 − TV) mmHg. TV is the ratio between the coefficient of variation of temperature during the nocturnal and the preceding diurnal periods. This result suggests that the circadian clock reflects brain plasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This magnetic field can act on human cryptochrome, a molecule involved in circadian rhythms and inflammation. 32 It has been found in clinical research that two days after geomagnetic storms, the risk of myocardial infarction with ST-elevation was over 1.5 times increased in some patients. 33 …”
Section: Discussionmentioning
confidence: 99%
“…This magnetic field can act on human cryptochrome, a molecule involved in circadian rhythms and inflammation. 32 It has been found in clinical research that two days after geomagnetic storms, the risk of myocardial infarction with ST-elevation was over 1.5 times increased in some patients. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Translocator Like (ARNTL, BMAL1), Period Circadian Regulators (PERs), Cryptochrome Circadian Regulators (CRYs). Disturbance of these clock genes lead to pathophysiology for cardiovascular system, whereas the stabilization is protective [47]. Although On the contrary, CovS-miR-21 from BNT162b2 would limit innate immunity via decreasing of ARNTL in circadian-rhythm [54,55].…”
Section: Circadian Rhythm Controller Of Covs-mir-21mentioning
confidence: 99%
“…Subsequently, since CoVS-miR-21 was a viral pathogenic factor, adenovirus-or vaccinia virus-based DNA vaccines should consider additional side-effects of SARS-CoV-2 S-derived miRNAs as circadian rhythm disturber because SARS-CoV-2 S DNA in adenovirus vector may be integrated into the host chromosome as a character of viral vectors [6,58,59]. For example, as the relationship of subarachnoid hemorrhage to circadian oscillation via CRYs and PER2 has been widely studied [47,60,61] spontaneous brain injury may be induced by SARS-CoV-2 S-derived miRNA.…”
Section: Circadian Rhythm Controller Of Covs-mir-21mentioning
confidence: 99%
“…in monitors of intensive care unit (12,13). Similarly, the ratio between the mean skin temperature during sleep and the preceding wake period correlated with the probability of occurrence of seizure in the following day in epileptic children (10,11).…”
Section: Introductionmentioning
confidence: 96%
“…We previously showed that the adult human hypothalamus may participate in brain plasticity through the expression of markers related to the formation of new neurons (7)(8)(9). Next, we showed that the possible role of the hypothalamus in brain plasticity could be quantified (10)(11)(12)(13). Accordingly, the mean intracranial pressure may be predicted with 24 hours of antecedence in stroke cases by the analysis of the variability of body temperature registered Copyright © 2021, Author(s).…”
Section: Introductionmentioning
confidence: 99%